Thermoelectric effect and its dependence on molecular length and sequence in single DNA molecules - Yueqi Li (Nature Portfolio, 2016)
Understanding the thermoelectric effect of materials and molecules is important for understanding their charge transport properties. Here, the authors study the thermoelectric effect in single DNA molecules and show that the charge carrier properties are dependent on both the DNA length and sequence.